Analisis Faktor Resiko Diabetes Melitus Tipe 2 Pada Kelompok Umur Dewasa di Rumah Sakit Umum Royal Prima Ayahanda Periode Januari 2023 – Desember 2024 - Ginting's, Varian Christhoper; Baeha, Ferdinando Motuho; Novita, Cut Elvira (Syntax Literate, 2025)
Type 2 Diabetes Mellitus (Type 2 DM) is a chronic metabolic disease characterized by hyperglycemia due to insulin resistance and impaired insulin secretion. The disease is increasing in prevalence, especially in the adult age group, so it is important to identify the risk factors that play a role in the occurrence of Type 2 DM. This study aims to analyze the relationship of risk factors such as age, sex, history of hypertension, family history of DM, and body mass index (BMI) to the incidence of Type 2 DM in patients at Royal Prima Ayahanda Hospital Medan. This study uses an analytical observational design with a cross sectional approach. Data were obtained from the medical records of patients treated with a diagnosis of Type 2 DM in the period January 2023–December 2024. The sample was determined by purposive sampling technique, involving 44 patients aged 40–65 years who met the inclusion criteria. Data analysis was carried out using the chi-square test with the help of SPSS. The results showed that the majority of patients were in the age group of 50–59 years (47.7%), with a higher proportion of women (61.4%). Age, sex, and history of hypertension were not significantly associated with the incidence of Type 2 DM (p>0.05). In contrast, family history of DM (p=0.032) and BMI (p=0.012) showed a significant association with the incidence of Type 2 DM. Patients who are overweight and obese have a higher risk of developing Type 2 DM, as do individuals with a family history of DM. These findings confirm the importance of prevention through weight control and early detection in individuals with a family history of DM. This research is expected to be a reference for health workers in public education and risk factor-based interventions.